Isomer-Specific Monitoring of Sialylated N-Glycans Reveals Association of α2,3-Linked Sialic Acid Epitope With Behcet’s Disease - Seo, Nari; Lee, Hyunjun; Oh, Myung Jin; Kim, Ga Hyeon; Lee, Sang Gil; Ahn, Joong Kyong; Cha, Hoon-Suk; Kim, Kyoung Heon; Kim, Jaehan; An, Hyun Joo (Frontiers in Molecular Biosciences, 2021)
Behcet’s disease (BD) is an immune disease characterized by chronic and relapsing systemic vasculitis of unknown etiology, which can lead to blindness and even death. Despite continuous efforts to discover biomarkers for accurate and rapid diagnosis and optimal treatment of BD, there is still no signature marker with high sensitivity and high specificity. As the link between glycosylation and the immune system has been revealed, research on the immunological function of glycans is being actively conducted. In particular, sialic acids at the terminus of glycoconjugates are directly implicated in immune responses, cell–cell/pathogen interactions, and tumor progression. Therefore, changes in sialic acid epitope in the human body are spotlighted as a new indicator to monitor the onset and progression of immune diseases. Here, we performed global profiling of N-glycan compositions derived from the sera of 47 healthy donors and 47 BD patients using matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) to preferentially determine BD target glycans. Then, three sialylated biantennary N-glycans were further subjected to the separation of linkage isomers and quantification using porous graphitized carbon-liquid chromatography (PGC-LC)/multiple reaction monitoring (MRM)-MS. We were able to successfully identify 11 isomers with sialic acid epitopes from the three glycan compositions consisting of Hex5HexNAc4NeuAc1, Hex5HexNAc4Fuc1NeuAc1, and Hex5HexNAc4NeuAc2. Among them, three isomers almost completely distinguished BD from control with high sensitivity and specificity with an area under the curve (AUC) of 0.945, suggesting the potential as novel BD biomarkers. In particular, it was confirmed that α2,3-sialic acid at the terminus of biantennary N-glycan was the epitope associated with BD. In this study, we present a novel approach to elucidating the association between BD and glycosylation by tracing isomeric structures containing sialic acid epitopes. Isomer-specific glycan profiling is suitable for analysis of large clinical cohorts and may facilitate the introduction of diagnostic assays for other immune diseases.